Pengembangan Sistem Informasi Manajemen Pemesanan Pakaian dan Keuangan Berbasis Web (Studi Pada: YP Screenprinting) - Fitra Wahyuda; Satrio Agung Wicaksono; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
YP Screenprinting is one of the small and medium businesses (SMB) in Bojonegoro Regency which is engaged in convection. Most of the orders placed in the form of t-shirts are from inside and outside the city. The process of recording orders at Yp Screenprinting is still done manually and expenses for purchasing raw materials are not recorded. So that it causes problems such as difficulty in finding data orders or expenses and business owners can not know how much profit or loss is experienced with certainty. Based on these problems a solution is made in the form of a web-based information system to help simplify the process of managing orders and expenses. Making information systems is done using the system development life cycle (SDLC) in the form of the Waterfall method. In the requirements definition stage it produces 22 functional requirements. The software design stage uses the object oriented analysis design (OOAD) approach and the results are described using a unified modeling language (UML) which produces 3 controller classes and 4 model classes. At the implementation stage using the model view controller (MVC) as the system architecture. Finally in the system testing stage, the results are 100% valid in validation testing and 88.75% results in user acceptance testing. Based on the test results it can be said that the information system that has been made is well received by the user